Multidimensional Pain Inventory (MPI): Adaptation to Orthodontic Patients and Its Psychometric Properties - Campos, Lucas Arrais de (2019)
Background: Pain perception may result from orthodontic treatment and should be considered in clinical management. Its assessment should not be limited to the intensity of perceived pain but should also consider the psychosocial and behavioral aspects involved. Objective: The aims of this study were to adapt and validate the Multidimensional Pain Inventory (MPI) for orthodontic patients, and present a proposal to calculate an overall score of the pain-related aspects and compare these scores with the usual methodology used. Methods: Face validity of the MPI was estimated and orthodontic version (MPI-Orthodontic) was developed. Factorial validity was evaluated by confirmatory analysis. Convergent and discriminant validity and reliability were estimated. The fit of Second-Order Hierarchical Models was estimated. Concurrent validity of MPI-Orthodontic was evaluated against the Visual Analogue Scale. Invariance of the factorial models was evaluated for independent samples and according to sex and age. Overall score was calculated using the matrix of regression weights and compared to simple arithmetic mean. Results: 507 individuals (63.3% women; age: 26.32 (SD = 11.70) years) participated. For the fit of Part I (psychosocial aspects) of the MPI-Orthodontic, it added correlation between two items and excluded one item; for Part II (behavioral aspects) two items were excluded. The models presented adequate fit to the sample. Reliability was adequate. MPI-Orthodontic presented invariance for independent samples and adequate concurrent and divergent validity. Score obtained with the simple arithmetic mean was overestimated for Part I and underestimated for Part II. Conclusion: MPI-Orthodontic was valid, reliable and invariant for the evaluation of the orthodontic pain. It is recommended to calculate overall weighted scores for pain assessment.